Pengenalan dan Penggunaan Website Ujian Online Sebagai Media Pembelajaran Pada Siswa/Siswi SMA Negeri 1 STM Hilir - Soeb Aripin; Natalia Silalahi; Kurnia Ulfa (Journal of Social Responsibility Projects by Higher Education Forum, 2020)
The introduction and use of this Online Website for learning activities is aimed at making high school students able to learn easily by utilizing technology. In the introduction and use of the Online Exam Website, we will introduce and use the Online Exam Website, one of which is through the website "https://tryout.pendukasi.id". This training will be delivered in the form of presentations and demonstrations. Each of our explanations will also be followed by brief questions to ensure the children understand what we have said. As well as increasing knowledge on how to use this Online Exam Website, we hope that it can become knowledge as well as provision to be able to study independently and easily